PEDAGOGICAL DESIGN OF EDUCATIONAL PROGRAMS IN THE CONTEXT OF CONTINUING EDUCATION: STATE AND PROSPECTS - Оракова, Амангул; Наметкулова, Фарида; Корнилова Taтьяна; Жайтапова, Алтнай; Тургунбаева, Ботагуль (Pedagogy and Psychology, 2023)
The article was performed within the framework of the program-targeted grant of the Ministry of Education and Science of the Republic of Kazakhstan of the scientific and technical program OR 11465474 "Scientific foundations for the modernization of the education and science system" (2021-2023) under the leadership of the National Academy of Education. Y. Altynsarin, the purpose of which is to develop scientific and methodological foundations for the design of pedagogically oriented educational programs in the system of technical and vocational education, higher and postgraduate educational institutions. Within the framework of global changes, for the qualitative integration of the Kazakhstani education system into international educational markets, teachers need to be able to work in the new market conditions. In accordance with the state demand, it is important to train pedagogical staff capable of creativity and formed professional competence. This, in turn, leads to the relevance of improving non-formal education in education. In this regard, the Lifelong Learning (LLL) Memorandum on Lifelong Learning in Education of the European Union has been adopted as a key guiding strategic concept. The paper examines the importance of pedagogical design for the formation and development of functional literacy and professional competences of learners in the design of educational programmes. In addition, the results of the analysis of scientific-theoretical materials revealed that in the definition of "Pedagogical Design" scientists denoted it as a science, process, subject, system, whereas the authors of the article consider it as a tool. The state of pedagogical design of educational programmes in the context of lifelong learning is analysed and priorities for its further application are identified.